Florida Bears and Beekeeping - Malcolm T. Sanford; James D. Ellis (EDIS, 2012)
The Florida black bear (Ursus americanus floridanus) is a minor predator of beehives in Florida with the potential to cause major destruction. Large-scale urban and agricultural development inexorably reduces prime bear habitat each year. This habitat also contains excellent bee forage, and so bears and bees will sometimes come in contact, thus resulting in bear predation. This revised 2-page fact sheet was written by Malcolm T. Sanford and James D. Ellis, and published by the UF Department of Entomology and Nematology, August 2012.